Pembelajaran BIPA yang berorientasi pada aktivitas pemelajar di KBRI Kopenhagen 2021 - Boy Tri Rizky (Jurnal Bahasa Indonesia bagi Penutur Asing, 2022)
This study aims to describe the application of student action-oriented learning in BIPA 2 Class at the Indonesian Embassy in Copenhagen. Action-oriented learning is an approach that has become the standard of the CEFR (Common European Framework of Reference for Languages). The curriculum system and Indonesian Language Competency Standards for Foreign Speakers (SKL BIPA) adapt the curriculum from the CEFR, therefore this approach can be considered in teaching BIPA abroad, especially in Europe. This research is descriptive qualitative research, this research describes in detail and in-depth the portrait of conditions in a natural context (natural setting), about what actually happened according to what was in the field of study in the application of a learning approach oriented to student action in the classroom BIPA 2 of the Indonesian Embassy in Copenhagen. The results showed that it is easy to use this action-oriented approach because this approach is already known for foreign language learning in Europe. There are 3 phases in the lesson, namely the contextualization phase, development phase, and processing phase. In the contextualization phase, students can update and build contexts in their reflections on the topics to be learned.  In the development phase, students begin to develop their language skills. In the processing phase, students no longer have language barriers that limit their creativity. Through this approach, students can be more active in learning Indonesian language because there are lots of media that require them to be active in class.